2000
DOI: 10.1177/016344300022001003
|View full text |Cite
|
Sign up to set email alerts
|

Public relations, news production and changing patterns of source access in the British national media

Abstract: This article aims to draw attention to the rising influence of professional public relations on the process of national news production in Britain and to discuss how this influence is affecting existing media-source relations. It notes that a wide range of organizations have begun adopting public relations as a means of achieving particular goals through media coverage. At the same time media institutions, operating under tighter editorial budgets, have become more dependent on information supplied by external… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
1
10

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(127 citation statements)
references
References 14 publications
3
113
1
10
Order By: Relevance
“…Our participants' responses reflect the findings of previous research which acknowledges tensions between government and media actors centered on: access to resources (Davis, 2000), 'knowledge and authority' (Savage and Tiffen, 2007:83) and contests for agenda setting and influence (Wolfsfeld, 1997). Several journalists commented that these tensions had increased with the growth in number of GIOs since devolution, and with what they saw as the rise of manipulative public relations strategies such as spin and evasion.…”
Section: Working Relationships Between Gios Spads and Journalistssupporting
confidence: 75%
“…Our participants' responses reflect the findings of previous research which acknowledges tensions between government and media actors centered on: access to resources (Davis, 2000), 'knowledge and authority' (Savage and Tiffen, 2007:83) and contests for agenda setting and influence (Wolfsfeld, 1997). Several journalists commented that these tensions had increased with the growth in number of GIOs since devolution, and with what they saw as the rise of manipulative public relations strategies such as spin and evasion.…”
Section: Working Relationships Between Gios Spads and Journalistssupporting
confidence: 75%
“…Gans (1979Gans ( , 2003 and Davis (2000) fi nd that it is the politicians, while Strömbäck and Nord (2006, p. 147) conclude that "it is the journalists not their political sources that lead the tango most of the time".…”
Section: Journalist-politician Relations and News Reportingmentioning
confidence: 99%
“…Likewise, Davis (2000) found that the British media are becoming increasingly dependent on information supplied by external sources due to tighter editorial budgets. In the Netherlands, journalists are less likely to follow politicians' views; yet, politicians tend to prevail since they very often seem to succeed in getting media attention and coverage (Brants et al, 2010, p. 37).…”
Section: Journalist-politician Relations and News Reportingmentioning
confidence: 99%
See 1 more Smart Citation
“…PRÁctIcAs De RePORteO: lA PAsIVIDAD en lA cultuRA PeRIODÍstIcA cOntInÚA Los análisis de los estudiosos de la transformación de los medios en México constantemente han omitido una observación más fina de las prácticas de reporteo y de relación con sus fuentes y con sus colegas de otros medios que sí existen en otros países (Sigal, 1973;Davis, 2000Davis, y 2009. El periodista debe asumirse no solo como individuo con su propia carga de valores y principios (pragmáticos o teóricos), sino también como una entidad profesional colectiva en la que se desempeña en conjunto con sus colegas y competidores en una fuente informativa específica para la que los proveedores de información y sujetos noticiosos son fundamentales.…”
Section: Roles Profesionales En Conflictounclassified